Climate and environment in southwest Sweden 15.5–11.3 cal. ka BP. (15th March 2018) - Wohlfarth, Barbara; Luoto, Tomi P.; Muschitiello, Francesco; Väliranta, Minna; Björck, Svante; Davies, Siwan M.; Kylander, Malin; Ljung, Karl; Reimer, Paula J.; Smittenberg, Rienk H.
Abstract : Lake sedimentary records that allow documentation of the distinct climatic and environmental shifts during the early part of the Last Termination are scarce for northern Europe. This multi‐proxy study of the sediments of Atteköpsmosse, southwest Sweden, therefore fills an important gap and provides detailed information regarding past hydroclimatic conditions and local environmental responses to climatic shifts. Lake infilling started c . 15.5 cal. ka BP, but low aquatic productivity, cold summer lake water temperatures, unstable catchments, and scarce herb and shrub vegetation prevailed until c . 14.7–14.5 cal. ka BP. Inflow of warmer air masses and higher July air temperatures favoured a rise in aquatic productivity and lake water summer temperatures, and the establishment of a diverse herb, shrub and dwarf shrub vegetation, which also included tree birch c . 14.5 cal. ka BP. Freshening of the moisture source region c . 13.7–13.6 cal. ka BP does not seem to have had a large impact on the ancient lake and its catchment, as lake aquatic productivity increased further and lake water summer temperatures and minimum mean July air temperatures remained around 12–14 °C. In contrast, further freshening of the moisture source region c.  13 cal. ka BP triggered a decrease in lake productivity, drier conditions and lower lake water summer temperatures. Macroscopic finds of tree Betula and Pinus sylvestris at 13–12.8 cal. ka BP demonstrate the presence of these trees in the lake's catchment. The transition into the Holocene (11.6–11.5 cal. ka BP) is marked by a change in chironomid assemblages and by a rise in lake water summer temperatures and aquatic productivity. These changes were followed by the re‐establishment of a diverse aquatic and terrestrial vegetation, including tree birch and Pinus sylvestris at 11.4 cal. ka BP.